Talking with José Ignacio González Faus. (Journal of Parents and Teachers, 2014)
In this article, José Ignacio González Faus, the academic director of the Center for Studies "Christianity and Justice", interviews José Ignacio González Faus, who offers his point of view on what contemporary religion should be, on the role of women in different religions or the future of the multireligious reality in Spain, among others.
Keywords: Interview; José Ignacio González Faus; religion.